A History of modern drama volume II, 1960-2000 - Krasner, David 1952- (Chichester, West Sussex, UK Wiley Blackwell, 2016)
A History of Modern Drama: Volume II explores a remarkable breadth of topics and analytical approaches to the dramatic works, authors, and transitional events and movements that shaped world drama from 1960 through to the dawn of the new millennium.
Includes bibliographical references and indexes.
Keywords: Drama -- 20th century -- History and criticism